PEMANFAATAN DANA ZAKAT OLEH BADAN AMIL ZAKAT NASIONAL DALAM PEMBERDAYAAN MASYARAKAT MISKIN DI KABUPATEN BANTAENG PROVINSI SULAWESI SELATAN - Yayat Sudrajat; Andi Muh. Ilham Jaya (ipdn, 2019)
Utilization of Zakat Funds by the National Zakat Agency in Empowering the Poor in Bantaeng District, South Sulawesi Province. The aim of this research is to find out, how to empower the poor through the utilization of zakat funds by Baznas Bantaeng Regency; What are the inhibiting factors in the empowerment, as well as how to overcome obstacles related to the empowerment of the poor through the use of zakat funds. This research is a qualitative descriptive study with an inductive approach. Data was collected by triangulation techniques, namely observation, interviews and documentation. Data analysis is done by presenting data, reducing data and drawing conclusions. The results of this study indicate that: the empowerment of the poor through the use of zakat funds carried out by the Baznas in Bantaeng Regency has gone well and has directly touched the poor. The inhibiting factor in empowering the poor can be categorized as minimal because it only comes from a lack of personnel as well as direct assistance. Keywords: empowerment, zakat, baznas, bantaeng.